Genocide as Social Practice : Reorganizing Society under the Nazis and Argentina's Military Juntas - Feierstein, Daniel, 1967- (Book collections on Project MUSE., 2014)
"Genocide not only annihilates people but also destroys and reorganizes social relations, using terror as a method. In Genocide as Social Practice, social scientist Daniel Feierstein looks at the policies of state-sponsored repression pursued by the Argentine military dictatorship against political opponents between 1976 and 1983 and those pursued by the Third Reich between 1933 and 1945. He finds similarities, not in the extent of the horror but in terms of the goals of the perpetrators. First published in Argentina, in Spanish, Genocide as Social Practice has since been translated into many languages, now including this English edition. The book provides a distinctive and valuable look at genocide through the lens of Latin America as well as Europe."--Publisher's description